Religious unbelief and literature: The novels of Graham Greene - Frontera Izquierdo, Pedro (Razón y fe, 2022)
The reflection in current literature of the growing problem of religious unbelief and especially of one of its types, indifference, is described. It is compared with the literature of the middle of the 20th century, and the most significant novels of the most relevant catholic writer, Graham Greene, whose 30th anniversary of his death is being celebrated, are analyzed. The difficulties of the necessary new evangelization to combat religious indifference and the strategy of introduction in the wide field of culture and specifically in literature are discussed.